2023
DOI: 10.3390/ijms24065725
|View full text |Cite
|
Sign up to set email alerts
|

METTL3-Mediated LncRNA EN_42575 m6A Modification Alleviates CPB2 Toxin-Induced Damage in IPEC-J2 Cells

Abstract: Long non-coding RNAs (lncRNAs) modified by n6-methyladenosine (m6A) have been implicated in the development and progression of several diseases. However, the mechanism responsible for the role of m6A-modified lncRNAs in Clostridium perfringens type C piglet diarrhea has remained largely unknown. We previously developed an in vitro model of CPB2 toxin-induced piglet diarrhea in IPEC-J2 cells. In addition, we previously performed RNA immunoprecipitation sequencing (MeRIP-seq), which demonstrated lncRNA EN_42575 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…M 6 A modification of mRNA affects its stability, splicing, translation, and nuclear transport [30]. M 6 A modification of lncRNAs also can affect their expression, such as METTL3 mediated the expression of LINC00958 and lncRNA EN_42575 [38,39]. In the present study, a total of 20 overlapping lncRNAs were found in DE lncRNAs and DM lncRNAs.…”
Section: A C C E P T E Dsupporting
confidence: 46%
“…M 6 A modification of mRNA affects its stability, splicing, translation, and nuclear transport [30]. M 6 A modification of lncRNAs also can affect their expression, such as METTL3 mediated the expression of LINC00958 and lncRNA EN_42575 [38,39]. In the present study, a total of 20 overlapping lncRNAs were found in DE lncRNAs and DM lncRNAs.…”
Section: A C C E P T E Dsupporting
confidence: 46%